Media Discourse in an Atmosphere of Information Warfare: From Manipulation to Aggression - Vladimir I Ozyumenko (Russian journal of linguistics: Vestnik RUDN, 2017)
In todays atmosphere of information warfare the biased impact of the media has increased, pushing behind other functions, including the informative one. The forms of media influence have also changed: direct persuasion has been replaced by implicit manipulation, which develops into outright aggression. Since, in the media discourse aggression can be both verbal and non-verbal, we propose to use the term information (or media) aggression , which is broader than verbal aggression . Media aggression can be considered as a binary process - in relation to the referent (affective aggression) and in relation to the audience (cognitive aggression). As a result, the information under media aggression refers to the expression of open hostility and animosity towards the referent and meaningful impact on the consciousness of the recipient (the target audience) to its ideological subordination. The purpose of this article is to justify the hypothesis that the growing media aggression is a feature of modern media discourse in the atmosphere of information warfare, and this function can be analysed within the framework of manipulative discourse as manipulative persuasion. The data has been taken from quality British and American newspapers, news websites of The BBC, The Economist, The Guardian, The New York Times, The Washington Post, and some others covering the relations between Russia and the USA, the situation in the Middle East, particularly in Syria. The the study was conducted using critical discourse analysis (Fairclough 2001, Van Dijk 2006, 2009; Wodak 2007; Weiss, Wodak 2007) and the multimodal approach (Ivanova, Spodarets 2010; Ponton 2016), and reveals various strategies and means of linguistic manipulation and media aggression. It also shows that the main aim of linguistic manipulation accentuated by verbal and non-verbal aggression is to deliberately mislead the audience imposing on it the desired idea of ideological subordination. Therefore, a knowledge of the mechanisms of manipulative influence is essential to counter the information and psychological war.